Struktur Pesan pada Interactive Voice Response (IVR) - Winangsari Pradani (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2011)
Interactive Voice Response (IVR) is an automated telephony system that interacts with callers, gathers information and routes calls to the appropriate recipient. An IVR system (IVRS) accepts a combination of voice telephone input and touch-tone keypad selection and provides appropriate responses in the form of voice, fax, callback, e-mail and perhaps other media.  In recent years, many enterprises use IVR as their customer service media. Some problems arise as user problems, that is user have to remembering the too many choices; user does’nt achieve what  they want (did not find the right choices); and the worst is tiring finding choices yet they have not find the human operator. This paper will observe the effect of message structuring for IVR customer satisfication. Human information processing (especially audio-based information) theory as well as menu organizing theory will be used as analysis fundamentals. Questionnaire will be distributed to IVR users to grab the real user experience.